Use of a cellular ELISA for the detection of cell surface antigens - Bishop, G A (BioTechniques, 1992)
A sensitive, convenient and inexpensive enzyme-linked immunosorbent assay (ELISA) is described for the detection and relative quantitation of cell surface antigens. The cells to be tested are rapidly glutaraldehyde-fixed to the wells of microtiter plates, which can be stored for later assay, if desired. Alternatively, adherent cells may be left unfixed. Following incubation with antibodies specific for the antigens of interest, an enzyme-linked second antibody conjugate is added, followed by the substrate for the enzyme, as in a conventional ELISA for soluble proteins. The method is a sensitive and accurate alternative to immunofluorescence flow cytometry for rapid and inexpensive screening of large numbers of cell samples